Predictors of Gastrostomy Tube Placement in Head and Neck Cancer Patients at a Rural Tertiary Care Hospital - Copeland-Halperin, Libby R.; Divakar, Prashanthi; Stewart, Talia; Demsas, Falen; Levy, Joshua J.; Nigriny, John F.; Paydarfar, Joseph A. (Journal of Reconstructive Microsurgery Open, 2023)
Background Head and neck cancer is a leading cause of cancer. Treatment often requires surgical resection, free-flap reconstruction, radiation, and/or chemotherapy. Tumor burden and pain may limit swallowing and impair nutrition, increasing complications and mortality. Patients commonly require gastrostomy tubes (G-tube), but predicting which patients are in need remains elusive. This study identifies predictors of G-tube among head and neck cancer patients undergoing immediate free-flap reconstruction.Methods Institutional Review Board approval was obtained. Retrospective database review was performed of patients at 18 years of age or older with head and neck cancer who underwent resection with immediate free-flap reconstruction from 2011 to 2019. Patients who underwent nonfree-flap or delayed reconstruction or with mortality within 7 days postoperatively were excluded. Patient demographics and comorbidities, tumor/treatment characteristics, and need for G-tube were analyzed to identify univariate and multivariate predictors.Results In total, 107 patients were included and 72 required G-tube placement. On multivariate analysis, tracheostomy (odds ratio [OR]: 81.78; confidence interval [CI]: 7.43–1,399.92; p < 0.01), anterolateral thigh flap reconstruction (OR: 16.18; CI: 1.14–429.66; p = 0.04), and age 65 years or younger (OR: 9.35; CI: 1.47–89.11; p = 0.02) were predictors of G-tube placement.Conclusion Head and neck cancer treatment commonly involves extensive resection, reconstruction, and/or chemoradiation. These patients are at high risk for malnutrition and need G-tube. Determining who requires a pre- or postoperative G-tube remains a challenge. In this study, the need for tracheostomy or ALT flap reconstruction and age 65 years or younger were predictive of postoperative G-tube placement. Future research will guide a multidisciplinary perioperative pathway to facilitate the optimization of nutrition management.
Keywords: head and neck cancer; gastrostomy tube predictors; delayed reconstruction; free-flap reconstruction; malnutrition; flap-related complications